2018
DOI: 10.1002/lt.25307
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Donor Hepatectomy for Adult Living Donor Liver Transplantation Recipients

Abstract: Even after 2 decades of experience in laparoscopic hepatectomy, data on purely laparoscopic approach for donor hepatectomy in adult living donor liver transplantation (LDLT) are limited. We report our initial experience of a purely laparoscopic approach for donor hepatectomy for adult recipients to explore its potential application in the management of donors. We did a retrospective data analysis of 54 consecutive patients operated on between May 2013 and February 2015. There were 41 right, 10 extended right, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 29 publications
6
86
1
Order By: Relevance
“…We then returned to the restriction of any anatomical variations, and the expansion of the anatomical criteria required more experience. (19) In this study, the donor complication rate and duration of hospital stay in the propensity-matched population showed no significant differences between the 2 groups. However, this study could not evaluate the effect of donor anatomy on the recipient outcomes because we did not perform separate analyses according to the donor selection criteria.…”
Section: Original Article | 1649mentioning
confidence: 51%
See 1 more Smart Citation
“…We then returned to the restriction of any anatomical variations, and the expansion of the anatomical criteria required more experience. (19) In this study, the donor complication rate and duration of hospital stay in the propensity-matched population showed no significant differences between the 2 groups. However, this study could not evaluate the effect of donor anatomy on the recipient outcomes because we did not perform separate analyses according to the donor selection criteria.…”
Section: Original Article | 1649mentioning
confidence: 51%
“…Our initial expansion of anatomical criteria after the first 7 successful cases resulted in an increased complication rate. We then returned to the restriction of any anatomical variations, and the expansion of the anatomical criteria required more experience . In this study, the donor complication rate and duration of hospital stay in the propensity‐matched population showed no significant differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Pure laparoscopic procedures has several advantages compared to conventional open surgery, including less wound morbidity and faster recovery 21 . More recently, Kwon et al reported that, after careful donor selection, and using standardized surgical methods, pure laparoscopic donor hepatectomy for adult LDLT was safe and benefitted the donors 22 . Similarly, we found here (in the largest such study to date) that PLDRH donors had lower opioid requirements until postoperative day 7 than the ODRH donors.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several major liver transplant centers in Korea have started to present short-term results of LDRH based on sufficient experience. 13,14 Careful preparation and blood-saving surgery will signifi-A B C Fig. 4.…”
Section: Discussionmentioning
confidence: 99%